THE POTENTIAL OF COMMUNITY ACCEPTANCE ON UB-03 BIOMASS STOVE - Eza Yolan Yuswansyah; Agus Haryanto; Budianto Lanya; Tamrin . (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2013)
UB-03 stove is a modern and efficient stove fueled by solid biomass, like pieces of branches, corn stalks, pieces of scrap wood, palm shells, and trash briquettes.. The objective of this study was to determine the potential of community acceptance on UB-03’s biomass stove.  The research was conducted from February 2013 to March 2013 in  namely Way Halom village, Sub-district of Gunung Alip, District of Tanggamus and Sidosari village, Sub-district of Natar, District of South Lampung. The methods used in this study include direct interview, demonstration of using UB-03 stove, and questionnaires. Data collected together with stove appearance (model, performance, price) was used to analyze the influence of education level and income rate to community acceptance towards UB-03 stove. The results showed that people in Sidosari and Gisting (80% of respondents) potentially receive and willing to use the UB-03 stove.  In both villages, education level and income rate affected people willingness towards UB-03 stove.  Respondents with education level from elementary to high school were highly interested (80%) towards UB-03 stove. People having diploma degree and above, however, were less interested to the stove.  Communities with income rates between Rp.500.000, - up to Rp.2.000.000,- showed high willingness in using the stove. In Sidosari, people with income over Rp.2.000.000,- showed less interested.  Stove’s price that could be accepted in the two villages were in the range of Rp.35.000,- to Rp.75.000,-.Keywords: UB-03 Stove, willingness, appearance, price and form